Synthesis of naturally occurring bioactive butyrolactones: maculalactones A-C and nostoclide I - Kar, Anirban; Gogoi, Sanjib; N. P. Argade (Tetrahedron, 2005)
Starting from citraconic anhydride (13), a simple multistep (9-10 steps) synthesis of naturally occurring butyrolactones maculalactone A (3), maculalactone B (1), maculalactone C (2) and nostoclide 1 (4) have been described with good overall yields via dibenzylmaleic anhydride (20) and benzylisopropylmaleic anhydride (27). The two anhydrides 20 and 27 were prepared by S(N)2' coupling reactions of appropriate Grignard reagents with dimethyl bromomethylfumarate (14), LiOH-induced hydrolysis of esters to acids, bromination of carbon-carbon double bond, in situ dehydration followed by dehydrobromination and chemoselective allylic substitution of bromoatom in disubstituted anhydrides 19 and 26 with appropriate Grignard reagents. The NaBH4 reduction of these anhydrides 20 and 27 furnished the desired lactones 21 and 29, respectively. The lactone 21 on Knoevenagel condensation with benzaldehyde, furnished maculalactone B (1), which on isomerization gave maculalactone C (2). Selective catalytic hydrogenation of 1 gave maculalactone A (3). The conversion of lactone 29 to nostoclide 1 (4) is known. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: dimethyl bromomethylfumarate; disubstituted maleic anhydrides; maculalactone A-C; NaBH4 reductions; nostoclide 1; S(N)2 ` Grignard couplings; synthesis